Paja i Jare - kamiondžije - Ðukanović, Milo (Yugoslavia : Avala Film Beograd, 1973)
The film is a collage made from the popular classic comic TV-series following the adventures of experienced truck driver Paja and his younger driving assistant Jare, who work in a state transport company. When a new company policy is announced, requiring all employees to have completed at least primary education, Paja, who has worked in the firm for over 20 years, still thinks he can get away without going back to school again. But this time he is wrong, and rather than finishing his education and getting the necessary qualifications, Paja and Jara decide to leave the company and become private truckers in socialist Yugoslavia. Struggling at first, gradually through many comic situations they achieve success and even wealth, but only by breaking the law, and they are soon faced with jail sentences. After many plot twists, and not without pressure from his family, Jare realizes that he was doing much better in the original company and goes back to school. He is soon joined by Paja and the two of them study together and after further difficulties finally manage to pass the exams and return to work.
Keywords: Fiction films